The Growth Pattern and Condition Factors of Swanggi (Pracanthus tayenus Richardson, 1846) Landed at Coastal Fishing Port of Lempasing - Putri, Septi Malidda Eka; Putriani, Rizha Bery; Delis, Putu Cinthia; Kartini, Nidya (Jurnal Biologi Tropis, 2024)
Lempasing Coastal Fishery Port is one of the fishing ports in Lampung Province with one of the catches is Swanggi (Priacanthus tayenus) or local people call it king fish gantang. The purpose of this study was to determine the growth pattern and condition factors of Swanggi (Priacanthus tayenus) landed at the Lempasing Coastal Fishery Port as an effort to manage sustainable fishery resources. This research was conducted in May-August 2023. The method used in this research is the survey method. Sampling was done 8 times with an intensity of 2 weeks. Swanggi samples used are the result of fishermen's catch at PPP Lempasing. The results showed that male and female Swanggi had a negative allometric growth pattern. The condition factor value of male Swanggi in May-August 2023 is 1.0437; 0.9414; 1.01; 1.0057, respectively, while the female Swanggi obtained the average condition factor value is 1.4502; 0.9937; 0.9937; 1.0057.